Increased UHMWPE Particle-Induced Osteolysis in Fetuin-A-Deficient Mice - Christina Polan; Christina Brenner; Monika Herten; Gero Hilken; Florian Grabellus; Heinz-Lothar Meyer; Manuel Burggraf; Marcel Dudda; Willi Jahnen-Dechent; Christian Wedemeyer; Max Daniel Kauther (Journal of Functional Biomaterials, 2023)
Particle-induced osteolysis is a major cause of aseptic prosthetic loosening. Implant wear particles stimulate tissue macrophages inducing an aseptic inflammatory reaction, which ultimately results in bone loss. Fetuin-A is a key regulator of calcified matrix metabolism and an acute phase protein. We studied the influence of fetuin-A on particle-induced osteolysis in an established mouse model using fetuin-A-deficient mice. Ten fetuin-A-deficient (Ahsg−/−) mice and ten wild-type animals (Ahsg+/+) were assigned to test group receiving ultra-high molecular weight polyethylene (UHMWPE) particle implantation or to control group (sham surgery). After 14 days, bone metabolism parameters RANKL, osteoprotegerin (OPG), osteocalcin (OC), alkaline phosphatase (ALP), calcium, phosphate, and desoxypyridinoline (DPD) were examined. Bone volume was determined by microcomputed tomography (μCT); osteolytic regions and osteoclasts were histomorphometrically analyzed. After particle treatment, bone resorption was significantly increased in Ahsg−/− mice compared with corresponding Ahsg+/+ wild-type mice (p = 0.007). Eroded surface areas in Ahsg−/− mice were significantly increased (p = 0.002) compared with Ahsg+/+ mice, as well as the number of osteoclasts compared with control (p = 0.039). Fetuin-A deficiency revealed increased OPG (p = 0.002), and decreased levels of DPD (p = 0.038), OC (p = 0.036), ALP (p < 0.001), and Ca (p = 0.001) compared with wild-type animals. Under osteolytic conditions in Ahsg−/− mice, OPG was increased (p = 0.013), ALP (p = 0.015) and DPD (p = 0.012) were decreased compared with the Ahsg+/+ group. Osteolytic conditions lead to greater bone loss in fetuin-A-deficient mice compared with wild-type mice. Reduced fetuin-A serum levels may be a risk factor for particle-induced osteolysis while the protective effect of fetuin-A might be a future pathway for prophylaxis and treatment.